The Transitional Program for Socialist Revolution - Trotsky L.; Hansen Joseph; Novack George (New York Pathfinder Press, 1973)
Contains discussions between leaders of the U.S Socialist Workers Party and exiled revolutionary Leon Trotsky in 1938. The product of these discussions, a program of immediate, democratic and transitional demands, was adopted by the SWP later that year. This program for socialist revolution, remains an important tool for communist workers today.
Keywords: 32